Architectural interior systems : lighting, acoustics, air conditioning - Flynn, John E.; Kremers, Jack A. ;Segil, Arthur W.;Steffy, Gary R. (New York : Van Nostrand Reinhold Company, Inc., 1992)
A guide to applying building-system engineering and design considerations to aspects of the created environment that affect human sensory response, behavior, productivity, and impressions of well-being. A general reference for architects and interior designers, and suitable as an introductory text for students in those fields.
Preface -- Part 1.Sensory performance standards: basic spatial patterns -- 1. The luminous environment -- 2. Sonic environment -- 3. Thermal environment -- 4. Transition patterns -- Part 2. System performance and method: performance of materials, forms and individual systems -- 5. Light generation and control -- 6. Sound generation and control -- 7. Thermal and atmospheric control -- Part 3. Coordinated system development -- 8. The building as a comprehensive environmental system -- Index.
Includes bibliographical references and index.
Keywords: BUILDINGS